Redeemed by fire : the rise of popular Christianity in modern China - Lian Xi (New Haven : Yale University Press, 2010)
This text addresses the history and future of homegrown, mass Chinese Christianity. Drawing on a collection of sources, the author traces the transformation of Protestant Christianity in the 20th-century China from a small 'missionary' church buffeted by antiforeignism to an indigenous opular religion energized by nationalism.
In search of Chinese Christianity --The lightning out of the east : the True Jesus Church --The Jesus Family --The smitten land : China in revival --"Elucidating the way" : an independent preacher's revolt against mission churches --"Flame for God" : John Sung and the Bethel Band --Awaiting rapture : Watchman Nee and the Little Flock --The indigenous church movement through war and revolution --Cries in the wilderness : the underground church in the communist era.
Includes bibliographical references and index
Keywords: China -- Church history -- 20th century